(Re)structuring and (Re)imagining the First Year Experience for Graduate Students of Color Using Community Cultural Wealth - Ivan Valdovinos Gutierrez; Lillie Ko-Wong (MDPI AG, 2024)
Graduate students of color have been entering graduate schools at unprecedented rates, yet these programs and institutions are not ready to fully support their unique needs. Using Yosso's Community Cultural Wealth framework, we showcase how graduate students of color utilize their cultural capital to succeed during their first year of graduate studies. We interviewed 10 graduate students from various graduate programs in Southern California and found that graduate students of color activated all six forms of cultural capital to persist through the challenges of their first year in graduate education. As graduate students of color used various forms of cultural capital to combat oppressive systems and structures during their first year, we call on graduate school programs and institutions to restructure and reimagine what support looks like for first-year graduate students of color by using an assets-based approach.